The performance of membrane bioreactor treating high temperature wastewater - Salim, Mohd. Razman (2007)
Membrane bioreactor technology represents the most rapidly growing membrane technology in the water sector. In recent years, MBR technologies have been playing a very important role in water and wastewater treatment. MBRs are used to treat a wide range of municipal and industrial wastewaters. MBR integrates membrane filtration with biological degradation system of waste products. It is defined as a modification of the conventional activated sludge system (AS), where the separation of the treated water from the mixed liquor is accomplished by a membrane system instead of a clarifier. The two basic MBR process configurations are external and submerged. The high cost of pumping makes external MBR system impractical for full-scale municipal wastewater treatment plants. In this study, submerged MBR (SMBR) process was developed.